'The Rhino Horn on Display Has Been Replaced by a Replica': Museum Security in Finland and England. Issue 1 (16th March 2016) - Grove, Louise; Thomas, Suzie
Museums are an integral part of the cultural life of societies. As well as having intangible value, many collections may also have considerable financial value and present a temptation to thieves. Furthermore, threats exist from accidents, natural disasters, and vandalism, among many other risks that have to be taken into account when building up museums security measures. In recent years, high-profile art thefts from museums and even, regrettably, acts of terror have drawn attention to the vulnerability of museum institutions as sites of crime and catastrophe. In particular, balancing visitor enjoyment and accessibility of the exhibits with security can be difficult for many. Despite awareness of these concerns, museums security remains to date under-represented in museological discourses, perhaps in part because of its perceived pragmatic nature. Another reason may be the difficulty of discussing in a meaningful way information that is often confidential and sensitive. In this paper, based on research carried out in Finland and England, we aim to analyse some of the key issues for museums security, which, whilst observed in northern European settings, also have relevance for museums globally. We set this discussion against the backdrop of ethical considerations and present our methodology for gathering the data and for discussing our results in a way which is both sensitive to confidentiality issues and still of use to the wider security, museums, and cultural heritage sectors.